Cross-Gender Attempts by Indonesian Female Impersonator Dancer Didik Nini Thowok - Madoka Fukuoka (Wacana Seni Journal of Arts Discourse, 2014)
This article examines the creative stages of Didik Nini Thowok (1954?), a female impersonator and cross-gender dancer based in Java, Indonesia. In addition, it discusses his endeavours of crossing gender boundaries by focusing on his use of costumes and masks, and analysing two significant works: Dwimuka Jepindo as an example of comedic cross-gender expression and Dewi Sarak Jodag as an example of serious cross-gender expression. The findings indicate three overall approaches to crossing gender boundaries: (1) surpassing femininity naturally expressed by female dancers; (2) mastering and presenting female characters by female impersonators and cross-gender dancers; and (3) breaking down the framework of gender itself.